In vitro assessment of antimicrobial efficacy of the D‐tagatose and lactobacilli‐based synbiotic preparations against the pathogenic Escherichia coli and Salmonella typhimurium. (27th December 2020) - Roy, Sohini; Samanta, Ashis Kumar; Dhali, Arindam; Kolte, Atul Purushottam; Chikkerur, Jayaram; Bhatta, Raghavendra
Summary: The study aimed to investigate the utilisation of prebiotic D‐tagatose by probiotic lactobacilli ( L . rhamnosus GG, L . casei, L . acidophilus and L . fermentum ) and enteric pathogens ( E. coli and S. typhimurium ) to determine synbiotic potential of D‐tagatose and lactobacilli combination. The antimicrobial efficacy of the synbiotic preparations (D‐tagatose with lactobacillus) was assessed against selected pathogens in co‐culture assays. Evidently, D‐tagatose supported growth of selected lactobacilli, especially the L. rhamnosus GG and L. casei, but not the enteric pathogens. The tested synbiotic preparations completely inhibited growth of both the pathogens, even in the presence of D‐glucose in co‐cultures. The well‐diffusion assay demonstrated the presence of antimicrobial activity as recorded by drop of culture pH. The study substantiated that D‐tagatose could be an effective prebiotic component for formulation of potential synbiotic combinations with L. rhamnosus GG or L. casei that can be used as an alternative to antibiotics against enteric pathogens. Abstract : In batch cultures, D‐tagatose did not supported the growth of pathogens ( E. coli and S. typhimurium ). In Co‐cultures, D‐tagatose in combination with L. rhamnosus GG or L. casei effectively inhibited the growth of the pathogens. The inhibitory could be attributed to the drop in culture pH. This study revealed that the synbiotic combinations of D‐tagatose with L. rhamnosus GG or L. casei can be used as potential alternatives to antibiotics against E. coli and S. typhimurium .